Paracrine Factors Released by Stem Cells of Mesenchymal Origin and their Effects in Cardiovascular Disease: A Systematic Review of Pre-clinical Studies - Nishani S. Mabotuwana; Lavinia Rech; Joyce Lim; Sean A. Hardy; Lucy A. Murtha; Peter P. Rainer; Andrew J. Boyle (Stem Cell Reviews and Reports, 2022)
Mesenchymal stem cell (MSC) therapy has gained significant traction in the context of cardiovascular repair, and have been proposed to exert their regenerative effects via the secretion of paracrine factors. In this systematic review, we examined the literature and consolidated available evidence for the “paracrine hypothesis”. Two Ovid SP databases were searched using a strategy encompassing paracrine mediated MSC therapy in the context of ischemic heart disease. This yielded 86 articles which met the selection criteria for inclusion in this study. We found that the MSCs utilized in these articles were primarily derived from bone marrow, cardiac tissue, and adipose tissue. We identified 234 individual protective factors across these studies, including VEGF, HGF, and FGF2; which are proposed to exert their effects in a paracrine manner. The data collated in this systematic review identifies secreted paracrine factors that could decrease apoptosis, and increase angiogenesis, cell proliferation, and cell viability. These included studies have also demonstrated that the administration of MSCs and indirectly, their secreted factors can reduce infarct size, and improve left ventricular ejection fraction, contractility, compliance, and vessel density. Furthering our understanding of the way these factors mediate repair could lead to the identification of therapeutic targets for cardiac regeneration. Graphical abstract